Pancreatic cancer: Update on immunotherapies and algenpantucel-L. Issue 3 (3rd March 2016) - McCormick, Kinsey A.; Coveler, Andrew L.; Rossi, Gabriela R.; Vahanian, Nicholas N.; Link, Charles; Chiorean, E. Gabriela
ABSTRACT: Pancreatic adenocarcinoma is notoriously lethal, and despite improvements in systemic chemotherapy approaches bringing survival rates for metastatic disease to almost 1 year, by 2030 it is expected to become the second leading cause of cancer death. Pancreatic cancer (PC) prognosis has been associated with both the presence of intratumoral helper and cytotoxic T lymphocytes, as well as humoral immune responses to tumor associated antigens like mesothelin. It is well described that the PC microenvironment is characterized by a fibroinflammatory and immunosuppressive stroma. On these premises several immune-targeted strategies have been developed to harness the adaptable immune system with a goal of improving survival with little toxicity. Cancer vaccines involve the administration of tumor-associated antigens with the goal of inducing an endogenous anti-tumor response. Among several strategies discussed, we will focus on the algenpantucel-L (HyperAcute™ Pancreas) immunotherapy. Algenpantucel-L is a whole cell immunotherapy consisting of irradiated allogeneic PC cells genetically engineered to express the murine enzyme α(1, 3)-galactosyltransferase (αGT), which ultimately leads to hyperacute rejection with complement- and antibody-dependent cytotoxicity. While phase III data in the adjuvant treatment of pancreatic cancer are pending, phase II results have been encouraging, particularly for patients who demonstrated humoral immunologic responses. Novel strategies using immune checkpoint inhibitors, costimulatory antibodies, and combinations with cancer vaccines may overcome immunotolerance and improve treatment success.